2017
DOI: 10.5530/jcdr.2017.4.25
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Pattern and Hypertension Related Knowledge, Attitude and Practices among Diagnosed Patients of Hypertension Attending a Tertiary Care Hospital

Abstract: Context: Hypertension can be controlled by modifying lifestyle related risk factors and generating awareness about these risk factors among hypertensive patients. Aim: To assess the life style pattern, knowledge, attitude and practices related to hypertension among diagnosed patients of hypertension attending a tertiary care hospital. Materials and methods: Across sectional hospital based study was conducted in a tertiary care hospital during May and June 2014.102 diagnosed patients of hypertension attending t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…Regarding knowledge about risk factors of hypertension, we found that majority (69.3%) of the respondents replied intake of high salt and high fat diet followed by stress (65.1%), increasing age(40.6%), intake of excessive amount of alcohol (30.7%), inactivity (23.1%) and heredity (45.3%). The present study finding is consistent with study done in India by Patnaik et al, 6 which revealed that majority (61.8%) of the respondent had answered increased salt intake followed by 52% heredity, 43% no regualr exercise, 39.2% tobacco used and 28.4% alcohol consumption.…”
Section: Resultssupporting
confidence: 92%
“…Regarding knowledge about risk factors of hypertension, we found that majority (69.3%) of the respondents replied intake of high salt and high fat diet followed by stress (65.1%), increasing age(40.6%), intake of excessive amount of alcohol (30.7%), inactivity (23.1%) and heredity (45.3%). The present study finding is consistent with study done in India by Patnaik et al, 6 which revealed that majority (61.8%) of the respondent had answered increased salt intake followed by 52% heredity, 43% no regualr exercise, 39.2% tobacco used and 28.4% alcohol consumption.…”
Section: Resultssupporting
confidence: 92%
“…De forma similar Patnaik (2017), halla una asociación inversamente proporcional entre los estilos de vida y la hipertensión arterial; afirma que, con solo una modificación adecuada de la dieta, las modificaciones dietéticas y evitar la situación estresante, pueden obviar totalmente la necesidad de un tratamiento farmacológico. La intervención en forma de educación sobre el estilo de vida de los hipertensos es útil para aumentar la conciencia sobre los factores de riesgo modificables, esto les permitirá adoptar y practicar un estilo de vida saludable, lo que ayudará a controlar la presión arterial y evitar complicaciones relacionadas con la hipertensión (Ortega et al, 2016) (Okwuonu, Emmanuel y Ojimadu, 2014).…”
Section: Discussionunclassified
“…• Most NCD patients have poor adherence to treatment, however treatment adherence is better when compared to adherence to healthy lifestyle practices. 20,21 • All patients had discontinued the treatment for chronic diseases at some point of time since detection. Reasons for noncompliance were lack of money, lack of motivation, living far away from health care provider and difficulty to remember to take daily medication due to work or forgetfulness.…”
Section: Alcohol Consumptionmentioning
confidence: 99%